Application of nimodipine combined with statins in the treatment of subarachnoid haemorrhage - Zhang, Yu; Ma, Feifan; Gan, Ning; Xu, Zhijie; Jiao, Yang; Zhan, Jiancang (Journal of the Pakistan Medical Association, 2025)
Objective: To explore the clinical effect of nimodipine combined with statins in the treatment of subarachnoid haemorrhage. Method: The retrospective study was conducted at the Baoding Forensic Hospital, China, and comprised data of subarachnoid haemorrhage patients who were treated from March 2019 to March 2022. The patients were divided into two groups on the basis of the treatment method. Control group A was treated with nimodipine, while observation group B was treated with nimodipine combined with statins. Clinical efficacy of the groups were assessed and compared along with endothelin 1, calcitonin gene-related peptide, vascular endothelial growth factor and peroxiredoxin 2 levels at baseline and 7 days after the treatment. Also noted were mean blood flow velocity of cerebral artery and adverse reactions. Data was analysed using SPSS 22. Results: Of the 100 patients, 50(50%) were in group A; 35(70%) females and 15(30%) males with mean age 66.00±8.26 years. There were 50(50%) patients in group B; 32(64%) females and 18(36%) males with mean age 63.58±7.89 years. The overall response rate was 34(68%) in group A compared to 45(90%) in group B (p<0.05). Post-treatment, group B had lower levels of endothelin 1 and vascular endothelial growth factor, and higher levels of calcitonin gene-related peptide (p<0.05). The mean blood flow velocity of the cerebral arteries significantly decreased in both the groups, but it was slower in group B than group A (p<0.05). The expression levels of peroxiredoxin 2 increased in both the groups, with higher levels observed in group B (p<0.05). The incidence of adverse reactions in group B was 3(6%) compared to 10(20%) in group A (p<0.05). Conclusion: Nimodipine combined with statins was found to have good efficacy and higher safety profile in the treatment of subarachnoid haemorrhage. Key Words: Nimodipine, Statins, Subarachnoid haemorrhage, ET-1, PRX2.